Revitalizing Verbal Communication: Exploring the Linguistic Landscape of International BIPA Students - Zahra, Arsy; Tiawati, Refa Lina; Rahmat, Wahyudi (Universitas PGRI Sumatera Barat, 2023)
This research is motivated by the presence of international students from various countries with diverse cultures and varying language abilities compared to Indonesia. International students are those who come from outside Indonesia, meaning that Indonesian is not their first language. International BIPA students aim to master the four language skills, one of which is speaking. Therefore, international students need to have the ability to speak effectively and correctly in verbal or oral communication. The research aims to analyze the forms of grammar and vocabulary usage in the verbal communication of international BIPA students at Andalas University. This research is qualitative in nature with a descriptive methodology. The research respondents are international students currently engaged in learning activities at Andalas University. Data collection is conducted through observation, interviews, recording techniques, and note-taking. Data analysis is carried out using the interactive data analysis method developed by Miles and Huberman. Based on the data analysis and discussion, it is found that international BIPA students can understand and use grammar and vocabulary effectively in oral communication. They can comprehend and use grammar and vocabulary in spoken language, such as personal pronoun usage, noun phrase structure, negation words, simple sentence construction, question word usage, demonstrative pronoun usage, the verb